Steroids Decrease Prevalence of Positive Tuberculin Skin Test in Rheumatoid Arthritis: Implications on Anti-TNF Therapies - Shweta Agarwal; Siddharth Kumar Das; Girdhar G. Agarwal; Ragini Srivastava (Interdisciplinary Perspectives on Infectious Diseases)
Tuberculin skin test has been used as an indicator of latent tuberculosis in patients with Rheumatoid Arthritis (RA) before administration of biologicals. Effect of Disease modifying antirheumatic drugs (DMARDs) and steroids on the result of tuberculin skin test (TST) may have important implications in interpretation of results of this test. Objectives. To find the prevalence of positive TST in rheumatoid patients and the effect of standard treatment on the results of TST. Method. In this cross-sectional study two hundred and fifty patients of RA above 18 years of age, classified using 1987 ACR criteria for RA, were enrolled from rheumatology outdoor. Demographics, disease activity, disease duration, and therapy were recorded. All patients underwent TST. Results. Fifty-one (20.4%) patients were found to be tuberculin positive. Tuberculin positivity was not affected by MTX intake but it was significantly low in patients with recent steroid intake as compared to patients who had not taken steroids in last 3 months (3% versus 25%, P = 0.002). Conclusion. Prevalence of tuberculin positivity in patients with RA was found to be low. Results were not affected by methotrexate; however tuberculin skin test results in patients with recent use of steroids are likely to be negative.